2009
DOI: 10.2166/wst.2009.675
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cooling tower blowdown water containing silica, calcium and magnesium by electrocoagulation

Abstract: This research investigated the effectiveness of electrocoagulation using iron and aluminium electrodes for treating cooling tower blowdown (CTB) waters containing dissolved silica (Si(OH)(4)), Ca(2 + ) and Mg(2 + ). The removal of each target species was measured as a function of the coagulant dose in simulated CTB waters with initial pH values of 5, 7, and 9. Experiments were also performed to investigate the effect of antiscaling compounds and coagulation aids on hardness ion removal. Both iron and aluminum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Many literatures have suggested that electro coagulation (EC) is a promising technology for the removal of both dissolved [54,55] and colloidal silica [56][57][58] in the various water streams. Its basic principle is in-situ generation of metal ion species by sacrificial anodic reaction (Fig.…”
Section: Electro Coagulationmentioning
confidence: 99%
“…Many literatures have suggested that electro coagulation (EC) is a promising technology for the removal of both dissolved [54,55] and colloidal silica [56][57][58] in the various water streams. Its basic principle is in-situ generation of metal ion species by sacrificial anodic reaction (Fig.…”
Section: Electro Coagulationmentioning
confidence: 99%
“…The issue of dissolved silica in cooling towers has continued to receive attention since the project was started 1,2 . The approaches have included electrocoagulation and hybrid ion exchange resins.…”
Section: Figure 1 Proposed Ge Solution For the Use Of Impaired Watermentioning
confidence: 99%
“…Saha et al [10] evaluated the performance of electrochemical oxidation (EO) with a boron-doped diamond (BDD) anode to remove organic compounds (OCs) from CTB in the cooling tower. Liao et al [11] reported that the efficiency of hardness ion removal for the cooling tower blowdown in the cooling tower can be improved by the EC using Fe and Al electrodes, and the addition of coagulation aids.…”
Section: Introductionmentioning
confidence: 99%